Influence of vibrational kinetics in a low pressure capacitively coupled hydrogen discharge - Marques, L. (2003)
In this paper we present the self consistent coupling of a 2D model of a parallel plate radio frequency discharge in pure hydrogen with a homogeneous chemical kinetics model including H2(X1Σg+,v=0..14) molecules and hydrogen atoms H(n=1-5). The model can estimate the ground state atomic hydrogen density and it was found that the vibrational kinetics changes the H3+ ion density and coupled power to the discharge about 40% when comparing with previous estimates using a simplified kinetics.